Data Sharing — Is the Juice Worth the Squeeze? - Strom, Brian L; Buyse, Marc E; Hughes, John; Knoppers, Bartha M (The New England journal of medicine, 2016)
Making clinical trial data widely available is ethically imperative and scientifically justified, but the experience with clinicalstudydatarequest.com suggests that we need to find ways to improve the use and output of data-sharing projects before broadening the effort. The past few years have seen considerable interest in the sharing of patient-level data from clinical trials. There is a clear and logical “ethical and scientific imperative” 1 for doing so, to permit activities ranging from verification of the original analysis to testing of new hypotheses. This interest has resulted in many publications and meetings, attention from the Institute of Medicine, 2 proposed changes in journals’ policies, 3 and enormous effort from pharmaceutical sponsors and other groups to provide access to patient-level data. 4 It is critical that we learn from these early experiences as we move forward. Beginning in May 2013, GlaxoSmithKline made . . .